Government Institutional Support in Increasing the Productivity of Soybean Seed Breeders Indonesia - Bahari, Bahari; Saediman, Haji; Geo, Laode; Arif, Norma (International Journal of Economics and Financial Issues, 2019)
In general, this study was aimed to reveal the extent of government contributions in encouraging increased productivity of seed breeders in Southeast Sulawesi Indonesia. This study was conducted in Southeast Sulawesi using cross-sectional data from 81 respondents obtained by census. The results of the research data were analyzed descriptively and used the stochastic frontier analysis. The results of the analysis showed that the increase in soybean seed production was significantly affected by the area of land, SP36 / NPK Fertilizer, Increased labor for threshing, and labor for drying. Overall, soybean breeder farmers had not achieved maximum productivity because still had productivity gap of 15 percent. The role of the government that significantly increases production and productivity could be done through fertilizer input subsidy program, increase in land area, and increase the intensity of BPSB counseling / supervision in each planting season. For this reason, the government needs to ensure access, availability and price of fertilizer during the soybean growing season. In addition, the government can intensify assistance and supervision of farmers while increasing the adoption of agricultural mechanization technology in the process of threshing and drying of seeds. Keywords: Government institutional, Soybean Farm, Productivity, Soybean Seed Breeder, JEL Classifications: D02, Q16, D24, Q12 DOI: https://doi.org/10.32479/ijefi.8645